Evaluation of easy-to-implement anti-stress interventions in a series of N-of-1 trials: study protocol of the anti-stress intervention among physicians study - Vetter, Valentin Max; Kurth, Tobias; Konigorski, Stefan (Frontiers in Psychiatry, 2024)
Adverse effects of chronically high levels of stress on physical and mental health are well established. In physicians, the effects of elevated stress levels exceed the individual level and include treatment errors and reduced quality of patient-doctor relationships. Breathing and mindfulness-based exercises have been shown to reduce stress and could serve as an immediate and easy-to-implement anti-stress intervention among physicians. Due to the heterogeneity of their effect on stress, we aim to evaluate the intervention effect of performing a short daily breathwork-based or mindfulness-based intervention on the everyday level of perceived stress in physicians in residence in Germany in a series of N-of-1 trials.Study participants will choose between two short interventions, box breathing, and one guided more complex mindfulness-based breathing exercise. Each participant subsequently will be randomly allocated to a sequence of 1-week intervention (A) and control (B, everyday life) phases. Each N-of-1 trial consists of two two-week cycles (AB or BA), resulting in a total trial duration of 4 weeks (ABAB or BABA). Perceived levels of stress will be assessed daily via the StudyU App on the participant's smartphone. Additionally, participants will be asked to complete a questionnaire at baseline and three months after completion of the study that contains questions about basic participant characteristics, lifestyle factors, individual living situations, and validated psychological questionnaires. Intervention effects will be estimated by Bayesian multi-level random effects models on the individual and population level.This study contributes to the development of short-term solutions to reduce work-related stress for physicians in residence. This is expected to benefit the individual and increase the quality of overall healthcare due to a reduction in treatment errors and an increase in the quality of doctor-patient relationships. Trial Registraion: ClinicalTrials.gov: NCT06368791, first registered April 16, 2024.